2007
DOI: 10.1007/s11332-007-0031-5
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhydrating with glycerol: effects on thermoregulation, hydration and athletic performance during specific exergonic exercise in a warm-humid environment

Abstract: We investigated the effects of hyperhydration with glycerol vs. water on athletic performance under hot-humid conditions (30% relative humidity and 36°C). During a 10-day acclimation period, 14 competitive male oarsmen performed 90 minutes of exercise at 260-W. On the eleventh day, athletes hydrated by consuming in 90 minutes a nutrient drink with or without glycerol. After hydration, athletes were tested three times with 250-400-W workloads in 30-W steps, at 15-min intervals. During the 250-400-W tests, athle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…However, one of those seven did show a potentially practical, albeit non‐significant, performance improvement of 9% 10 . One further study showed improved power at the anaerobic threshold with pre‐exercise glycerol hyperhydration and additional glycerol during exercise, as discussed in the next section 55 . Importantly, none of the studies showed a decrement in endurance performance following glycerol hyperhydration.…”
Section: Performance Effects Of Glycerol Hyperhydrationmentioning
confidence: 91%
See 3 more Smart Citations
“…However, one of those seven did show a potentially practical, albeit non‐significant, performance improvement of 9% 10 . One further study showed improved power at the anaerobic threshold with pre‐exercise glycerol hyperhydration and additional glycerol during exercise, as discussed in the next section 55 . Importantly, none of the studies showed a decrement in endurance performance following glycerol hyperhydration.…”
Section: Performance Effects Of Glycerol Hyperhydrationmentioning
confidence: 91%
“…Thirteen of the studies discussed in the previous section also investigated the effects of pre‐exercise glycerol hyperhydration on aspects of endurance exercise performance (Tables 2 and 3). Six of the 13 (including one with two series of experiments) showed significant improvements in endurance performance parameters, 7,8,13,16,53,56 while seven did not 10,17,18,20,21,54,55 . However, one of those seven did show a potentially practical, albeit non‐significant, performance improvement of 9% 10 .…”
Section: Performance Effects Of Glycerol Hyperhydrationmentioning
confidence: 94%
See 2 more Smart Citations
“…Most often, glycerol consumption is evaluated in acute exercise sessions, predominantly observing the hydration aspects (Dini et al 2007;Mehmet and Hüsrev 2011). Further, in a previous study, glycerol supplementation promoted increased use of circulating lipids in rats subjected to 6 weeks of training ).…”
Section: Introductionmentioning
confidence: 99%